Extracellular Electron Uptake by Acetogenic Bacteria: Does H2 Consumption Favor the H2 Evolution Reaction on a Cathode or Metallic Iron? - Philips, Jo (Frontiers in Microbiology, 2020)
Some acetogenic bacteria are capable of using solid electron donors, such as a cathode or metallic iron (Fe(0)). Acetogens using a cathode as electron donor are of interest for novel applications such as microbial electrosynthesis, while microorganisms using Fe(0) as electron donor cause detrimental microbial induced corrosion. The capacity to use solid electron donors strongly differs between acetogenic strains, which likely relates to their extracellular electron transfer (EET) mechanism. Different EET mechanisms have been proposed for acetogenic bacteria, including a direct mechanism and a H2 dependent indirect mechanism combined with extracellular hydrogenases catalyzing the H2 evolution reaction on the cathode or Fe(0) surface. Interestingly, low H2 partial pressures often prevail during acetogenesis with solid electron donors. Hence, an additional mechanism is here proposed: the maintenance of low H2 partial pressures by microbial H2 consumption, which thermodynamically favors the H2 evolution reaction on the cathode or Fe(0) surface. This work elaborates how the H2 partial pressure affects the H2 evolution onset potential and the H2 evolution rate on a cathode, as well as the free energy change of the anoxic corrosion reaction. In addition, the H2 consumption characteristics, i.e. H2 threshold (thermodynamic limit for H2 consumption) and H2 consumption kinetic parameters, of acetogenic bacteria are reviewed and evidence is discussed for strongly different H2 consumption characteristics. Different acetogenic strains are thus expected to maintain different H2 partial pressures on a cathode or Fe(0) surface, while those that maintain lower H2 pressures (lower H2 threshold, higher H2 affinity) more strongly increase the H2 evolution reaction. Consequently, I hypothesize that the different capacities of acetogenic bacteria to use solid electron donors are related to differences in their H2 consumption characteristics. The focus of this work is on acetogenic bacteria, but similar considerations are likely also relevant for other hydrogenotrophic microorganisms.